# Which of the following systems is dependent? Ox-y= 2 and x + y=-2 x-y= 2 and -2x + 2y=-4 O x-y=2 and

Which of the following systems is dependent?
Ox-y= 2 and x + y=-2
x-y= 2 and -2x + 2y=-4
O x-y=2 and 3x – 3y = 2
x-y= 2 and -x- y=-2

## This Post Has 10 Comments

1. shadowangel84 says:

c

Step-by-step explanation:

most of the people will spam to get points

2. reaperdraws says:

no solution

Step-by-step explanation:

hope this helped have a great day 😀

3. baseballdude4807 says:

there is not a solution to that problem

so it would be A

4. mohd591 says:

a

Step-by-step explanation:

5. raul2372 says:

(4, 2)

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

Brackets Parenthesis Exponents Multiplication Division Addition Subtraction Left to Right

Equality Properties

Algebra I

TermsSolving systems of equations using substitution/elimination

Step-by-step explanation:

Step 1: Define Systems

-2x + 2y = -4

2x - 3y = 2

Step 2: Rewrite Systems

2x - 3y = 2

Add 3y to both sides:                    2x = 3y + 2

Step 3: Redefine Systems

-2x + 2y = -4

2x = 3y + 2

Step 4: Solve for y

Substitution

Substitute in 2x:                    -(3y + 2) + 2y = -4Distribute -1:                           -3y - 2 + 2y = -4Combine like terms:              -y - 2 = -4Isolate y term:                        -y = -2Isolate y:                                 y = 2

Step 5: Solve for x

Define equation:                    2x - 3y = 2Substitute in y:                       2x - 3(2) = 2Multiply:                                  2x - 6 = 2Isolate x term:                        2x = 8Isolate x:                                 x = 4

6. 21hendlill says:

Arrange in slope intercept form
2y = 2x -4
y = x - 2

So, the line would go upcrossing the y axis at -2hope this helps

7. thebrain1345 says:

x=4, y=2 (4,2)

Step-by-step explanation:

This is a system of equations.

-2x+2y=-4

2x-3y=2

I'll use the elimination method to solve this.

what's left:

-y=-2

multiply both by -1

y=2

now, substitute 2 as y into one of the other equations.

For example:

-2x+2(2)=-4

-2x+4=-4

-2x=-8

x=4

hope this helps!

8. klpatrick853 says:

no solution

Step-by-step explanation:

To put the first equation into standard form, with the coefficients mutually prime, divide it by 5:

... x - y = 4

To put the second equation into standard form, with the coefficients mutually prime and the leading coefficient positive, divide by -2:

... x - y = 2

These are inconsistent equations, hence have no solution.

9. evazquez says:

(x, y) = (-2, -4)

Step-by-step explanation:

I like to start by putting the equations into standard form. That requires removing any common factors and making the leading coefficient positive.

-2x +2y = -4   ⇒   x -y = 2 . . . . . . divide by -2

3x +3y = -18   ⇒   x +y = -6 . . . . . divide by 3

__

Now, we can add these two equations to eliminate y:

(x -y) +(x +y) = (2) +(-6)

2x = -4 . . . . simplify

x = -2 . . . . . divide by 2

Substituting into the second equation gives ...

-2 +y = -6

y = -4 . . . . . add 2

The solution to the system of equations is (x, y) = (-2, -4).

$Find the solution to the system of equation -2x+2y=-4 3x+3y=-18$

10. midhin says:

x=0 and y=−2

keep scrolling it is kind of long

Step-by-step explanation:

−2x+2y=−4,3x−2y=4

−2x+2y=−4for x:

−2x+2y=−4

−2x+2y+−2y=−4+−2y

−2x=−2y−4

-2x/-2=-2y-4/-2

x=y+2

Substitute y +2 for x in3x−2y=4:

3x−2y=4

3(y+2)−2y=4

y+6=4

y+6+−6=4+−6

y=−2

Substitute −2 for y in x=y+2:

x=y+2

x=−2+2

x=0

x=0 and y=−2